Economical and technical efficiencies evaluation of full scale piggery wastewater treatment BNR plants - Oa, S W (Water science and technology : a journal of the International Association on Water Pollution Research, 2009)
A method evaluating the economic efficiency of piggery waste treatment plant based on kinetics for nitrogen removal performances is executed in this study and five full scale plants were evaluated, monitored intensively during one year under steady-state conditions. The performance data from those surveyed plants were recalculated by first-order kinetic equation instead of the Monod's equation, and the nitrogen removal kinetics related with COD/TKN ratios. Two plants adapting two extreme strategies for pre treatment, 'excess phase separation', and 'minimum phase separation', were evaluated by the assessment of life cycle cost (LCC). Although the compared two plants use an opposite strategy to each other, similar evaluation results are deduced by nitrogen removal efficiencies and operational and construction costs. But the proportions of constituent elements are as different as two opposite strategies, so electrical and construction costs are inversely proportional to chemical costs and operational costs respectively